Critical Role of Endoplasmic Reticulum Aminopeptidase 1 in Determining the Length and Sequence of Peptides Bound and Presented by HLA–B27. Issue 2 (February 2014) - Chen, Liye; Fischer, Roman; Peng, Yanchun; Reeves, Emma; McHugh, Kirsty; Ternette, Nicola; Hanke, Tomas; Dong, Tao; Elliott, Tim; Shastri, Nilabh; Kollnberger, Simon; James, Edward; et al.
<x xml:space="preserve">Abstract</x> Objective HLA–B27 and endoplasmic reticulum aminopeptidase 1 (ERAP1) are the two strongest genetic factors predisposing to ankylosing spondylitis (AS). A key aminopeptidase in class I major histocompatibility complex presentation, ERAP1 potentially contributes to the pathogenesis of AS by altering HLA–B27 peptide presentation. The aim of this study was to analyze the effects of ERAP1 on the HLA–B27 peptide repertoire and peptide presentation to cytotoxic T lymphocytes (CTLs). Methods ERAP1‐silenced and ‐competent HeLa.B27 and C1R.B27 cells were isotope‐labeled, mixed, lysed, and then immunoprecipitated using W6/32 or ME1 antibodies. Peptides bound to HLA–B27 were eluted and analyzed by tandem mass spectrometry. Selected peptides were synthesized and tested for HLA–B27 binding ability. The effect of ERAP1 silencing/mutation on presentation of an immunodominant viral HLA–B27 epitope, KK10, to CTLs was also studied. Results In both HeLa.B27 and C1R.B27 cells, the proportion of 9‐mer HLA–B27–bound peptides was decreased by ERAP1 silencing, whereas the percentages of longer peptides (11–13 mer) were increased. Surprisingly, following ERAP1 silencing, C‐terminally extended peptides were readily identified. These were better able to bind to HLA–B27 than were N‐terminally extended peptides lacking an arginine at position 2. In both HeLa.B27 cells and mouse fibroblasts expressing HLA–B27, the absence of ERAP1 reduced peptide recognition by HLA–B27–restricted KK10‐specific CTLs following infection with recombinant vaccinia virus or transfection with minigenes expressing KK10 precursors. Presence of an AS‐protective variant of ERAP1, K528R, as compared to wild‐type ERAP1, reduced the peptide recognition by KK10 CTLs following transfection with extended KK10 minigenes. Conclusion These results show that ERAP1 directly alters peptide binding and presentation by HLA–B27, thus demonstrating a potential pathogenic mechanism in AS. Inhibition of ERAP1 could potentially be used for treatment of AS and other ERAP1‐associated diseases.